The TCF7L2 locus and type 1 diabetes - Polychronakos Constantin; Qu Hui-Qi (BMC, 2007)
Abstract Background TCF7L2 belongs to a subfamily of TCF7-like HMG box-containing transcription factors, and maps to human chromosome 10q25.3. A recent study identified genetic association of type 2 diabetes (T2D) with this gene, correlated with diminished insulin secretion. This study aimed to investigate the possibility of genetic association between TCF7L2 and type 1 diabetes (T1D). Methods The SNP most significantly associated with T2D, rs7903146, was genotyped in 886 T1D nuclear family trios with ethnic backgrounds of mixed European descent. Results This study found no T1D association with, and no age-of-onset effect from rs7903146. Conclusion This study suggests that a T2D mechanism mediated by TCF7L2 does not participate in the etiology of T1D.